Interview with Odd Hoftun - Thanju, Jeewan P. (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
Mr. Odd Hoftun toiled more than 50 years in various development activities in Nepal mainly in development of Mission Hospital, Tansen, Palpa, Butwal Technical Institute (BTI) in Butwal; and later in the hydropower development in Butwal and neighbouring Districts of Nepal. He has been instrumental in training several hundreds of skilled technical manpower and establising high value companies such as Butwal Power Company, BTI, Nepal Hydro & Electric Ltd. (NHE), Himal Hydro and General Construction etc. He talked with Jeewan P. Thanju, Editor-in-Chief of HYDRO Nepal. DOI: http://dx.doi.org/10.3126/hn.v8i0.4932 Hydro Nepal: Journal of Water, Energy and Environment Issue No. 8, 2011 January Page: 81-83 Uploaded date: 23 June, 2011